Faktor-faktor penyebab tunggakan cukai tanah di daerah kecil Sungai Siput - Abdul Rahim, Nasd Rahayu (2013)
Quit-Rent collections are amongst the responsibilities handled by Sungai Siput Land & District Office. It is also known land tax, which is charged on an annual basis to all land owners and is the main income for the Perak State Government. However if this is not imposed strictly or not managed properly and accordingly to the law governing the whole process, there will be repercussion and issues that will arises. For example, one of the immediate effect will be delays and arrear of payments of the Quit-Rent charges by landowners. This research is to recognize and analyze the main cause of arrears and delays in Sungai Siput Sub- District, and to refine the current process and propose improvements plans to overcome these issues especially those involves in the process in delays, arrears in payments, public (landowners) awareness and lack of responsibilities in making payments, data discrepancies in the Land Revenue Collection System (SPHT), land (title) inheritance and ownerships issues and others Quit-Rent collections activities